HEALTH TECHNOLOGY PERFORMANCE ASSESSMENT: REAL-WORLD EVIDENCE FOR PUBLIC HEALTHCARE SUSTAINABILITY. (23rd June 2017) - Guerra-Júnior, Augusto Afonso; Pires de Lemos, Lívia Lovato; Godman, Brian; Bennie, Marion; Osorio-de-Castro, Cláudia Garcia Serpa; Alvares, Juliana; Heaney, Aine; Vassallo, Carlos Alberto; Wettermark, Björn; Benguria-Arrate, Gaizka; Gutierrez-Ibarluzea, Iñaki; Santos, Vania Cristina Canuto; et al.
Abstract : Objectives: Health technology financing is often based on randomized controlled trials (RCTs), which are often the same ones used for licensing. Because they are designed to show the best possible results, typically Phase III studies are conducted under ideal and highly controlled conditions. Consequently, it is not surprising that technologies do not always perform in real life in the same way as controlled conditions. Because financing (and price paid) decisions can be made with overestimated results, health authorities need to ask whether health systems achieve the results they expect when they choose to pay for a technology. The optimal way to answer this question is to assess the performance of financed technologies in real-world settings. Health technology performance assessment (HTpA) refers to the systematic evaluation of the properties, effects, and/or impact of a health intervention or health technology in the real world to provide information for investment/disinvestment decisions and clinical guideline updates. The objective is to describe the development and principal aspects of the Guideline for HTpA commissioned by the Brazilian Ministry of Health. Methods: Our methods used include extensive literature review, refinement with experts across countries, and public consultation. Results: A comprehensive guideline was developed, which has been adopted by the Brazilian government. Conclusion: We believe the guideline, with its particular focus on disinvestment, along with the creation of a specific program for HTpA, will allow the institutionalization and continuous improvement of the scientific methods to use real-world evidence to optimize available resources not only in Brazil but across countries.